2018
DOI: 10.18502/sjms.v13i3.2961
|View full text |Cite
|
Sign up to set email alerts
|

The Response, Operability, and Type of Surgery Following Neoadjuvant Chemotherapy in Sudanese Patients with Locally Advanced Breast Cancer

Abstract: Background: Neoadjuvant chemotherapy (NACT) treatment has become the standard treatment for locally advanced breast cancer (LABC) in many centers worldwide. Objectives:This study evaluates the short-term response of patients with LABC to NACT and its impact on operability and the type of surgery. Patients and Methods:This is a descriptive analytical hospital-based study including 147 patients with LABC who were presented to Plastic and Reconstructive Surgery Unit at Soba University hospital (SUH), between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Mohammed et al . [ 19 ] in this randomized study observed that following NACT, CR was seen in 30 (20.4%) patients, PR in 92 (62.6%) patients, SD in 20 (13.6%) patients and 5 (3.4%) patients had PD. Out of these pCR was achieved in 25 (17%) patients, pPR in 102 (74.1%) patients and pSD in 13 (8.8%) patients.…”
Section: Discussionmentioning
confidence: 91%
“…Mohammed et al . [ 19 ] in this randomized study observed that following NACT, CR was seen in 30 (20.4%) patients, PR in 92 (62.6%) patients, SD in 20 (13.6%) patients and 5 (3.4%) patients had PD. Out of these pCR was achieved in 25 (17%) patients, pPR in 102 (74.1%) patients and pSD in 13 (8.8%) patients.…”
Section: Discussionmentioning
confidence: 91%